Early signet ring cell carcinoma of the stomach is related to favorable prognosis and low incidence of lymph node metastasis. Issue 5 (26th August 2016) - Imamura, Taisuke; Komatsu, Shuhei; Ichikawa, Daisuke; Kawaguchi, Tsutomu; Kosuga, Toshiyuki; Okamoto, Kazuma; Konishi, Hirotaka; Shiozaki, Atsushi; Fujiwara, Hitoshi; Otsuji, Eigo
Abstract : Background: The aim of this study was to evaluate the clinical characteristics of early signet ring cell carcinoma of the stomach (SRC) and to investigate the optimal treatment strategy for early SRC. Methods: A total of 746 patients with pT1 gastric cancer (GC), who had undergone surgical resection between 1997 and 2012 were analyzed. Of these, 190 patients with SRC were enrolled in this study. Results: (i) The patients with SRC showed a significantly longer overall survival ( P  = 0.012) and disease free survival ( P  = 0.004) than patients with the other histological types. Multivariate analysis identified SRC as an independent factor predicting favorable prognosis in pT1 GC (HR = 0.38; 95% CI: 0.11–0.96; P  = 0.041). Specifically, in undifferentiated pT1 GC, SRC was significantly less associated with lymph node metastasis (LNM) (OR = 0.39; 95% CI: 0.15–0.96; P  = 0.042). (ii) From the viewpoint of a histological mixed‐type, pure‐SRC with pT1a was not associated with LNM regardless of tumor size (0.0%, 0/110), whereas mixed‐SRC was an independent risk factor for LNM (OR = 7.19; 95% CI: 1.51–43.9; P  = 0.012). Conclusions: Patients with early SRC have a favorable prognosis with a low incidence of LNM. However, care should be taken with mixed‐SRC, which consists of SRC and other histological types. J. Surg. Oncol. 2016;114:607–612 . © 2016 Wiley Periodicals, Inc.